1973
DOI: 10.1073/pnas.70.8.2313
|View full text |Cite
|
Sign up to set email alerts
|

Self-association of Cholesterol in Aqueous Solution

Abstract: Cholesterol has a maximum solubility in aqueous solutions of 1.8 jug/ml or 4.7 ,M. It undergoes a thermodynamically reversible self-association with a critical micelle concentration of 25 to 40 nM at 250. The cholesterol micelle is heterogeneous in size, probably rodlike in shape, and stabilized by an unusually high interaction energy between the aggregated monomers.A critical problem in biochemistry today is the elucidation of the molecular organization of lipid and protein components in biological membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
0
3

Year Published

1988
1988
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(158 citation statements)
references
References 8 publications
(5 reference statements)
12
143
0
3
Order By: Relevance
“…However, we cannot exclude the possibility that ChOOH could not access the XfOhr active site, because this molecule can form micelles. Indeed, the parental compound (cholesterol) presents very a low CMC (25-40 nM) (36). On the other hand, because Triton X-100 and Tween-20 at least partly solubilize ChOOH (30), our results ( (Fig.…”
Section: Resultssupporting
confidence: 62%
“…However, we cannot exclude the possibility that ChOOH could not access the XfOhr active site, because this molecule can form micelles. Indeed, the parental compound (cholesterol) presents very a low CMC (25-40 nM) (36). On the other hand, because Triton X-100 and Tween-20 at least partly solubilize ChOOH (30), our results ( (Fig.…”
Section: Resultssupporting
confidence: 62%
“…In the case of cholesterol, it was necessary to work at concentrations above its reported aqueous CMC of 30-40 nM [46] in order to detect SPR responses (Fig. 6A).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively strong binding of cholesterol sulfate is likely to arise from its solubility properties, rather than its intrinsic affinity for NPC2. Haberland and Reynolds (35) have reported that cholesterol has a strong propensity to aggregate in aqueous solution, with a critical micelle concentration of ϳ25 nM, and have discussed how binding of cholesterol to a protein is a balance between the free energy gained from association with that protein and the free energy gained from self-association. It is likely that cholesterol sulfate is less prone to aggregation than cholesterol itself and that this alone may explain the greater apparent affinity of the negatively charged ligand for NPC2.…”
Section: Discussionmentioning
confidence: 99%